2008
DOI: 10.1186/1471-2261-8-12
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome and the immediate antihypertensive effects of aerobic exercise: a randomized control design

Abstract: BackgroundThe metabolic syndrome (Msyn) affects about 40% of those with hypertension. The Msyn and hypertension have a common pathophysiology. Exercise is recommended for their treatment, prevention and control. The influence of the Msyn on the antihypertensive effects of aerobic exercise is not known. We examined the influence of the Msyn on the blood pressure (BP) response following low (LIGHT, 40% peak oxygen consumption, VO2peak) and moderate (MODERATE, 60% VO2peak) intensity, aerobic exercise.MethodsSubje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
1
18
0
1
Order By: Relevance
“…Interestingly, some investigators 55 reported that obese subjects without the metabolic syndrome had more pronounced benefits of weight loss-induced BP reduction than those with the metabolic syndrome. We previously observed blunted responses of plasma NE and insulin to oral glucose ingestion in subjects with insulin resistance, 40,56 suggesting that exercise amelioration on insulin resistance may be an ancillary effect on weight loss-induced BP reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some investigators 55 reported that obese subjects without the metabolic syndrome had more pronounced benefits of weight loss-induced BP reduction than those with the metabolic syndrome. We previously observed blunted responses of plasma NE and insulin to oral glucose ingestion in subjects with insulin resistance, 40,56 suggesting that exercise amelioration on insulin resistance may be an ancillary effect on weight loss-induced BP reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several studies did not report a significant BP reduction over the 24-h period after aerobic exercise in normotensive young women (Forjaz et al, 1998;Pescatello et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…4 [2011] risk factor (e.g., blood pressure, CRP, glucose, insulin, HDL, LDL) with significant differences over the 12-week aquatic exercise protocol. The significant increases in glucose over time were small but unexpected since exercise training has been shown to decrease glucose concentrations in healthy and disease populations (Hansen et al, 2009;Pescatello et al, 2008). Currently, there is no clear explanation for the slight increases in blood glucose concentrations.…”
mentioning
confidence: 99%